Characterization of the Care Process for Hypertensive People in a Polyclinic in Old Havana - Addys Díaz Piñera; Yamila Soler Carbonell; Nelsy Álvarez Mesa; Armando Rodríguez Salvá (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: arterial hypertension is the most common of all conditions internationally and one of the main risk factors that contributes to premature mortality. Objective: to describe the epidemiological behavior of arterial hypertension and some elements of the care process at the Ángel Arturo Aballi Polyclinic, in the Old Havana municipality, from September 2019 to May 2020. Method: a descriptive and cross-sectional study was carried out in 159 people aged 18 years and over classified as hypertensive, to whom a questionnaire was applied to explore sociodemographic aspects, personal history and others related to the care process. Three blood pressure measurements were made at different times. The results were expressed in absolute and relative frequency. Results: 62.3 % of hypertensive people were older than 60 years, 61.6 % female. The most frequent comorbidities were: diabetes mellitus with 21.4 % and chronic obstructive pulmonary disease and asthma in 9.4 %. 54.7 % of these people did not feel the need for care in the last year and only 45.3 % were seen in a follow-up consultation. 81.8 % had not had their blood pressure measured for more than a year, 89.3 % had indicated drug treatment, 86.2 % were controlled and 74.6 % adhered to the treatment. Conclusions: the attention that these people received was not adequate; there were difficulties with dispensing, compliance with the program, in addition to a low perception of risk in these people.